Effective Parenting Patterns for Children's Religious Education in Divorced Families - Aisyah, Siti; Rahman, Mhd. Habibu (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
One of the impacts of divorce is a change in parenting patterns and its effect on children's religious education within the family. This research aims to identify parenting patterns in applying religious education within divorced Muslim families. Qualitative research approach with the case study method, research location in Laumulgap Village, Selesai District, Langkat Regency, North Sumatra. The informants were selected using purposive sampling, specifically three parents and three children from divorced Muslim families. Data collection techniques were carried out thru in-depth interviews with open-ended, semi-structured questions. Data analysis and management were conducted using Lincoln and Guba's naturalistic paradigm, with an emphasis on four data quality criteria: credibility, transferability, dependability, and confirmability. The research results show that the backgrounds of divorce are diverse, ranging from economic factors leading to infidelity by the wife, infidelity by the husband, families without conflict, and differences in life principles. These factors influence the level of conflict before and after divorce, thereby affecting the impact on the child's religious activities. The impact of divorce on children's religious behavior, such as abandoning worship and experiencing a spiritual crisis. Conversely, conflict-free divorce with active involvement from both parents does not show a negative impact on children's religiosity. The parenting styles employed also vary, ranging from permissive and authoritarian to democratic. The democratic parenting style has proven to be the most effective in guiding children thru the emotional and spiritual crises following divorce. This research emphasizes the importance of maintaining emotional stability and consistency in parenting for children's religious education. The quality of the parent-child relationship and parenting approaches after divorce are determining factors in the formation and recovery of children's religious behavior.